The Effects of Salvianolate Combined With Western Medicine on Diabetic Nephropathy: A Systematic Review and Meta-Analysis - Shen, Yuehong; Wang, Shulin; Liu, Yuanyuan; Ge, Ling; Xia, Lili; Zhang, Xiaoxiao; Miao, Yuying; Shen, Jianping; Zhou, Qian (Frontiers in Pharmacology, 2020)
Bacground: Salvianolate, a compound mainly composed of salvia magnesium acetate, is extracted from traditional Chinese medicine salvia. Because of the active ingredients, easy quality control and stable efficacy, salvianolate is widely used in ischemic cardio-cerebral vascular disease, liver and kidney damage, and diabetes, as well as its complications, especially the potential protective effects on diabetic nephropathy. Objective: The aim of this meta-analysis was to evaluate the exact efficacy and safety of salvianolate combined with western medicine in diabetic nephropathy patients. Methods: We searched Pubmed, Web of Science, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Data knowledge service platform (Wanfang Data), Chinese Scientific Journal Database (VIP), and China Biology Medicine Disc (SinoMed) for related literatures in periodical papers, degree papers and conference papers. The retrieval time was from the foundation of each database to November 30, 2019. Randomized controlled trials (RCTs) of salvianolate in combination with western medicine for diabetic nephropathy were adopted. Two reviewers independently performed literature screening, data extraction and quality evaluation. This meta-analysis was carried out by RevMan5.3 software. Results: A total of 1030 patients in China were involved in 12 RCTs. Meta-analysis showed that compared with using western medicine alone, combination of salvianolate for diabetic nephropathy could reduce serum creatinine [MD=-16.53, 95% CI (-28.79,-4.27), Z=2.64, P=0.008], blood urea nitrogen [MD=-1.40, 95% CI (-2.17,-0.62), Z=3.52, P=0.0004], urinary albumin excretion rate [SMD=-1.84, 95% CI (-2.70,-0.98), Z=4.19, P<0.0001], hypersensitive C-reactive protein [MD=-5.69, 95% CI (-7.09,-4.29), P<0.00001], Interleukin-6 [MD=-12.53, 95% CI (-18.55,-6.52), P<0.0001], malondialdehyde [SMD=-2.05, 95% CI (-3.67,-0.43), P=0.01], improve clinical efficacy [RR=1.21, 95% CI (1.12,1.31), Z=4.62, P<0.00001], and increase superoxide dismutase [SMD=1.12, 95% CI (0.86,1.38), P<0.00001]. Besides, treatment group hardly raised the occurrence of adverse events compared with control group. Conclusion: The combination of salvianolate with western medicine can protect renal function, reduce urinary albumin excretion rate, inhibit inflammation and perform antioxidation, thereby improving clinical efficacy. Thus, salvianolate can be considered as supporting treatmeng for diabetic nephropathy patients. However, due to the low quality of methodology and small sample effect, more rigorious and higher-level research is desirable.